Molecular Epidemiology of Tuberculosis in Foreign-Born Persons Living in San Francisco - Suwanpimolkul, Gompol; Jarlsberg, Leah G.; Grinsdale, Jennifer A.; Osmond, Dennis; Kawamura, L. Masae; Hopewell, Philip C.; Kato-Maeda, Midori (American journal of respiratory and critical care medicine, 2013)
In San Francisco, 70% of the tuberculosis cases occur among foreign-born persons, mainly from China, the Philippines, and Mexico. We postulate that there are differences in the characteristics and risk factors for tuberculosis among these populations. To determine the clinical, epidemiological and microbiological characteristics of tuberculosis caused by recent infection and rapid evolution in the major groups of foreign-born and the U.S.-born populations. We analyzed data from a 20-year prospective community-based study of the molecular epidemiology of tuberculosis in San Francisco. We included all culture-positive tuberculosis cases in the City during the study period. We calculated and compared incidence rates, clinical and microbiological characteristics, and risk factors for being a secondary case between the various foreign-born and U.S.-born tuberculosis populations. Between 1991 and 2010, there were 4,058 new cases of tuberculosis, of which 1,226 (30%) were U.S.-born and 2,832 (70%) were foreign-born. A total of 3,278 (81%) were culture positive, of which 2,419 (74%) had complete data for analysis. The incidence rate, including the incidence rate of tuberculosis due to recent infection and rapid evolution, decreased significantly in the U.S.-born and the major foreign-born populations. The clinical and microbiological characteristics and the risk factors for tuberculosis due to recent infection differed among the groups. There are differences in the characteristics and the risk factors for tuberculosis due to recent transmission among the major foreign-born and U.S.-born populations in San Francisco. These differences should be considered for the design of targeted tuberculosis control interventions.